2013
DOI: 10.1111/aor.12235
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic Machine Perfusion Versus Cold Storage in the Rescuing of Livers From Non‐Heart‐Beating Donor Rats

Abstract: The aim of this work was to compare the efficiency of cold storage (CS) and hypothermic machine perfusion (HMP) methods of preserving grafts excised from non-heart-beating donors that had suffered 45 minutes of warm ischemia. We developed a new solution for HMP to use in liver transplantation, based on BES, gluconate, and polyethylene glycol (BGP-HMP solution). After 24 h of HMP or CS, livers were reperfused at 37°C with Krebs-Henseleit solution with added dextran. For both procedures, portal pressure and flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…After retrieving livers, livers in HOPE group were connected to the precooled perfusion device and perfused via the portal vein. Perfusion flow was maintained at 0.23 ml/min per gram (38). Perfusate was not actively oxygenated (39,40) and recirculated for 3 h (perfusate volume 100 ml).…”
Section: Dcd Model and Liver Procurementmentioning
confidence: 99%
“…After retrieving livers, livers in HOPE group were connected to the precooled perfusion device and perfused via the portal vein. Perfusion flow was maintained at 0.23 ml/min per gram (38). Perfusate was not actively oxygenated (39,40) and recirculated for 3 h (perfusate volume 100 ml).…”
Section: Dcd Model and Liver Procurementmentioning
confidence: 99%
“…Here, we aim to develop a new preservation solution capable of being used in all the abdominal organs as well as for static and dynamic preservation techniques. In a previous work, we evaluated our new BGP‐HMP solution using HMP to rescue rat livers from non–heart‐beating donors (NHBDs) and proved that this solution used only for preservation might lead to a lower degree of injury than the one observed after using HTK for SCS . In the present work, we compared our BGP‐HMP solution with HTK by using SCS, IPRL, and heterotopic reduced nonarterialized auxiliary rat liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance and recovery of metabolism after preservation is another important point to analyze. In our previous work, using the BGP‐HMP solution with HMP, we found that the production of bile was diminished in relation to the SCS group with HTK in livers obtained from NHBDs . In this work, we confirmed a comparable decrease in the amount of bile secretion/production in livers preserved with both solutions, suggesting that the injury produced at the hepatocyte/canalicular level was similar with both solutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations